(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
Statistically processed morphometric data of craniofacial region in children of I and II period of childhood and its compliance to the principle of gold section. It will compare the indicators of the child’s facial skeleton, which may provide a methodological basis for the development of anthropometric methods of diagnosis and reconstruction in medicine. Measures of proportions of craniofacial area of surgical interventions are important in surgical, orthodontic and orthopaedic dentistry